Evaluasi Program Ka Bandara (Minangkabau Ekpres) Sebagai Sarana Transportasi Publik - Khairi, Andrisk; Yusran, Rammadani (Lembaga Penelitian dan Pendidikan Mandala, 2021)
This study aims to analyze the Evaluation of the Airport Train Program (Minangkabau Ekpres) based on the foundation of Law No.23 of 2014 concerning Railways and the 2030 National Railway Master Plan (RipNas2030) which explains the goals and objectives of the Airport Railway program. This research was conducted because it saw the activities of airport train passengers who were still less interested. The research method used in the study used a qualitative approach with a descriptive method. Research informants Data were collected through interviews with informants, field observations and documentation studies. The results of this study aim to determine the conditions and problems experienced by managers and complaints from researchers